PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS ETNOMATEMATIKA CANDI DERMO SEBAGAI MEDIA PEMBELAJARAN MATERI BANGUN DATAR SDN ANGGASWANGI 2 - Nadia Putri Emilia; Dian Kusmaharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This development research aims to develop and determine the validity and practicality of the Dermo Temple ethnomathematics-based learning video material on flat shapes in class 1 of SDN Anggaswangi 2 Sidoarjo. Based on the research result; (1) this learning videos of ethnomathematics was developedusing 4D models until the develop stage; (2) the media feasibility test result on the language aspect were 93,33% with very feasible criteria, the media appearance aspect was 87,77% with very feasiable criteria, and the material aspect was 86,66% with very feasible criteria; and (3) the practiciality of the Dermo Temple ethnomathematics based learning video was 83,57% which showed very practically criteria.